UTILIZING YOUTUBE TO DEVELOP NURSING STUDENTS’ AUTONOMOUS LEARNING AND LISTENING COMPREHENSION: AN EXPERIMENTAL STUDY - Michael Recard; Sandra Sembel; Shinta Hasibuan (Universitas Pelita Harapan, 2020)
Industrial Revolution (IR) 4.0. is about dealing with digital-native students and developing autonomous learning. One possible strategy to deal with these issues is using YouTube as a tool for English language learning. There have been some studies discussing the effectiveness of using it, yet we still have niches; for instance, deeper and wider contexts and respondents. Thus, this study aims to examine students’ autonomy over their learning and whether YouTube can develop the listening comprehension skills of nursing students in a Faculty of Nursing in Tangerang. To achieve the first aim, quantitative and qualitative studies were conducted, while for the second aim, an experimental study was used. The experimental study involved an experimental group consisting of 16 students and a control group consisting of 16 students. The result shows that the participants consider YouTube as a useful support to develop their autonomy in learning English and YouTube video has been successful to develop their listening skills.